Student Performance Application in the Practice of Teaching Deaf Students Based on Reflective Maternal Method (RMM) - Murni Winarsih; Totok Bintoro; Riana Bagaskorowati; Umi Nanik (Universitas Pendidikan Ganesha, 2023)
Teaching skills are the main skills every teacher needs to produce a generation of quality teachers. But the fact is that the performance appraisal that has been going on so far has used manual performance appraisal with a rubric. It raises a problem, namely, the evaluation becomes complicated and inefficient. The research aims to develop student performance applications in deaf student learning by conducting a needs analysis of current student skills and the material and content needed. The research design used a quantitative descriptive survey method of 120 Special Education study program students. The survey contains subject-related questions, which were distributed to 120 students. The data analysis technique uses descriptive qualitative analysis. The results showed that the level of students' skills in the teaching practice of deaf students was in the sufficient category, namely 99 respondents (82.5%). Data from material analysis showed that 75 respondents (62.5%) strongly agreed, 31 respondents (25.8%) agreed, and 2 respondents (1.7%) disagreed. Data from the content analysis showed that 79 respondents (65.8%) strongly agreed, 24 respondents (20%) agreed, and 3 respondents (2.5%) disagreed. The development of performance applications is based on the results of a needs analysis based on digital technology to assess students' abilities in teaching deaf students.